"A Friend, A Nimble Mind, and a Book": Girls' Literary Criticism in Seventeen Magazine, 1958–1969. (16th October 2021) - ANDERSON, JILL
Abstract : This article argues that postwar Seventeen magazine, a publication deeply invested in enforcing heteronormativity and conventional models of girlhood and womanhood, was in fact a more complex and multivocal serial text whose editors actively sought out, cultivated, and published girls' creative and intellectual work. Seventeen 's teen-authored "Curl Up and Read" book review columns, published from 1958 through 1969, are examples of girls' creative intellectual labor, introducing Seventeen 's readers to fiction and nonfiction which ranged beyond the emerging "young-adult" literature of the period. Written by young people – including thirteen-year-old Eve Kosofsky (later Sedgwick) – who perceived Seventeen to be an important publication venue for critical work, the "Curl Up and Read" columns are literary products in their own right, not simply juvenilia. Seventeen provided these young authors the opportunity to publish their work in a forum which offered girl readers and writers opportunities for intellectual development and community.